Relationship of the use of mouthwashes with the decrease in the viral load of SARS-CoV-2 in dental practice: topic review - Taboada-Granados, Miguel Alessandro; Colina-Neyra, Esteban Mauricio; Ruiz-Ramirez, Eliberto (Revista Facultad de Odontología Universidad de Antioquia, 2021)
It is currently known that the dentist is one of the health professionals with the highest risk of contagion of COVID-19 due to its direct contact with the oral cavity. High exposure to aerosols generated by rotating instruments in COVID-19 patients increases contact with the SARS-CoV-2 viral load in routine procedures. It has been described that mouthwashes prior to dental care could be effective solutions to reduce contagion despite their little clinical evidence. Mouthwashes with cetylpyridinium chloride (CPC), hydrogen peroxide (H2O2), povidone-iodine (PVP-I) and chlorhexidine gluconate (CHX) show great potential to reduce the viral load of SARS-CoV-2 in the aerosols generated from saliva during the dental visit. Therefore, the objective of this article was to review the current scientific information on the relationship of the use of mouthwashes with the decrease in the viral load of SARS-CoV-2.